The clinical challenges of synthetic cathinones. Issue 3 (3rd February 2020) - Schifano, Fabrizio; Napoletano, Flavia; Arillotta, Davide; Zangani, Caroline; Gilgar, Liam; Guirguis, Amira; Corkery, John Martin; Vento, Alessandro
Abstract : Aims: Within the new psychoactive substances (NPS) scenario, several hundred different molecules, mostly including synthetic cannabinoids and cathinones, have been identified so far. The aims of the paper were to: (i) identify the number of synthetic cathinones mentioned in a range of psychonaut, NPS‐related, online sources; and (ii) describe the associated acute/long term clinical scenario and the related treatment/management plan. Methods: After about 18 months of operation and exclusion of false positives/duplicates, some 4204 unique NPS molecules were included in the NPSfinder® crawling/navigating software database. Most popular NPS included: 1265 psychedelic phenethylamines (30.1%; confidence interval [CI] 95%: 28.7–31.5%); 1253 synthetic cannabinoids (29.8%; CI 95%: 28.4–31.2%); 429 synthetic opioids (10.2%; CI 95%: 9.3–10.2%); and 171 synthetic cathinones (4.1%; CI 95% 3.5–4.7%). Conversely, the United Nations Office on Drugs and Crime and the European Monitoring Centre for Drugs and Drug Addiction databases respectively included 169 and 140 cathinones. Overall, the 3 databases reported some 222 synthetic cathinones, and 41 were uniquely identified by the NPSfinder®. Results: In terms of clinical scenarios, synthetic cathinone ingestion is initially associated with stimulant effects; however, psychopathological disturbances, violence, suicidal behaviour, hyperthermia, coma and death have also been described. Conclusion: The proportion of cathinones commented on by psychonaut fora appeared to be relatively small, and similar to those reported by both the United Nations Office on Drugs and Crime and European Monitoring Centre for Drugs and Drug Addiction. This may be associated with a recent significant decline in both cathinone‐related consumption and acute medical presentation. Due to their complex behavioural and medical toxicity issues, healthcare professionals should be, however, be educated to recognise the signs and symptoms of NPS, including synthetic cathinone, ingestion.